Docker and Kubernetes for ASP.NET development - Williams, Trevoir (Packt Publishing, 2024)
This course is meticulously designed to take you on a journey from understanding the basics of containers to mastering the orchestration of applications using Kubernetes. We begin with an introduction to cloud-native development and explore a sample project to lay a solid foundation. You will learn about containers, their advantages over virtual machines, and get hands-on experience with Docker, including installation, configuration, and image management. Next, we delve into integrating Docker with .NET projects, where you'll containerize a .NET API, connect it to databases, and explore Dockerfile usage. Following this, you'll master Docker Compose, enabling you to manage multi-container applications efficiently. The course also covers advanced networking concepts, such as reverse proxies and SSL termination using NGINX, ensuring your applications are secure and scalable. Finally, we introduce Kubernetes, where you'll learn deployment strategies, manage resources, and scale applications. By the end of this course, you'll be able to seamlessly transition your .NET applications to modern containerized environments, leveraging both Docker and Kubernetes for efficient and scalable deployment.
Online resource; title from title details screen (O'Reilly, viewed June 24, 2024)
Keywords: Active server pages; Microsoft .NET Framework; Application software -- Development; Cloud computing; Logiciels d'application; Développement; Instructional films; Nonfiction films; Internet videos; Films de formation; Films autres que de fiction; Vidéos sur Internet